2022
DOI: 10.3390/cancers14215466
|View full text |Cite
|
Sign up to set email alerts
|

Speech and Language Errors during Awake Brain Surgery and Postoperative Language Outcome in Glioma Patients: A Systematic Review

Abstract: Awake craniotomy with direct electrical stimulation (DES) is the standard treatment for patients with gliomas in eloquent areas. Even though language is monitored carefully during surgery, many patients suffer from postoperative aphasia, with negative effects on their quality of life. Some perioperative factors are reported to influence postoperative language outcome. However, the influence of different intraoperative speech and language errors on language outcome is not clear. Therefore, we investigate this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…As a next step, we investigated the relation between different intraoperative speech and language errors and the postoperative language outcome in a separate second article based on the current systematic search [ 44 ]. This relation could be the foundation of a prognostic severity scale for speech and language errors on postoperative language outcome, which could guide the intraoperative procedure and may potentially reduce postoperative language deficits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a next step, we investigated the relation between different intraoperative speech and language errors and the postoperative language outcome in a separate second article based on the current systematic search [ 44 ]. This relation could be the foundation of a prognostic severity scale for speech and language errors on postoperative language outcome, which could guide the intraoperative procedure and may potentially reduce postoperative language deficits.…”
Section: Discussionmentioning
confidence: 99%
“…During data collection, it became apparent that there would be too much data to describe in one article. Therefore, the original outline as displayed on PROSPERO was divided into two, resulting in the current article (focusing on intraoperative speech and language errors and brain location) and a second article (focusing on intraoperative speech and language errors and language outcome [ 44 ]).…”
Section: Methodsmentioning
confidence: 99%
“…They also show that task‐specific preservation is possible. Identifying pre‐operative deficits is vital as they predict post‐operative language deficits up until 8 months after surgery (Bello et al., 2007; Collee et al., 2022; Ilmberger et al., 2008). Given that current neurofunctional models allow one to identify with imperfect but reasonable accuracy the language skills that may be damaged during surgery given the lesion site, in the interest of the patient it is preferable that all the at‐risk processes be evaluated, including reading and spelling, to improve functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…As regards spoken language, several studies identified a predictive value of the intra‐operative administration of object naming, word comprehension and/or the Pyramid and Palm Tree Test (PPTT) on acute post‐operative language functioning (Bello et al., 2007; Duffau et al., 2008). Moreover, a review of intra‐operative linguistic assessments in 81 studies showed that word‐finding difficulties and speech errors during surgery were significant predictors of post‐operative language deficits (Collee et al., 2022). However, since in most studies only spoken object naming was administered during surgery, the value of other tasks (including those that explore written language) in predicting post‐operative language outcome remains undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to neuromonitoring and preoperative deficits, intraoperative performance on selected tasks and/or positive mapping sites may also be associated with postoperative deficits [ 85 , 140 ]. A recent systematic review reported that intra-operative anomia and production errors were significantly predictive of postoperative language deficits in the acute phase (1 to 10 days), and when combined with a preoperative deficit, the probability further increased [ 140 ]. Importantly, these factors were not associated with postoperative deficits at 3 to 8 months.…”
Section: Managing Expected and Unexpected Intraoperative Eventsmentioning
confidence: 99%